The Problem with Bulgaria’s Lack of Funding Directed to the Education Sector - Милошев, Борис (Научни трудове, 2024)
Human capital is one of the driving factors for an economy and has a direct effect on production. One of the best ways to boost a country’s GDP is to increase labor productivity, which is directly linked with long-term economic growth. With Bulgaria having one of the lowest general government expenditures to GDP ratio in Europe and low teachers’ salary rates compared to other countries, it’s important to determine how this may be affecting the country and its economic growth as a whole. The aim of this paper is to analyze the lack of funding in the educational sector based on the human capital theory and the Augmented Solow growth model, as well as to provide some suggestions on possible improvement strategies.